Knowledge is power - Impact of interactive radio programming on women's empowerment and agricultural development outcomes in Malawi - Ragasa, Catherine (International Food Policy Research Institute, 2019)
Presented by Catherine Ragasa (International Food Policy Research Institute), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.